การศึกษาเนื้อหาและการใช้ประโยชน์จากนิตยสารวัยรุ่นในการเสริมความรู้และจริยธรรม - มนตรา สายวิวัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To study quantities and presentations of knowledge and moral contents in the following teenage magazines: Ice, The Boy and You&Me. Data is acquired through the content analysis of these magazines published during October 2001-September 2002 and surveying needs and opinion of 400 readers for their uses in knowledge and moral complement. Research findings are as follows: 1. Teenage magazines present knowledge about skin and figure tips the most and about drugs the least. In terms of moral content they present diligence the most and justice the least. 2. Teenage magazines present knowledge content in form of the article the most and the editorial the least. In term of moral content, they present in the form of actor s interview the most and there is no moral content in the form of demostration and reader s essay at all. 3. Readers want teenage magazines to present the knowledge about film, TV programme, music and books the most and about druge the least. And for moral content they want honest the most and diligence the least. They also want teenage magazines to present both of knowledge and moral contents in form of miscellaneous the most and the editorial the least. 4. Teenage magazines readers gain knowledge complement in medium level and moral complement in high level.